Climate variables along a traverse line in Dronning Maud Land, East Antarctica - van den Broeke, Michiel R; Winther, Jan-Gunnar; Isaksson, Elisabeth; Pinglot, Jean Francis; Karlöf, Lars; Eiken, Trond; Louk, Conrads (Journal of Glaciology, 1999)
Temperature, density and accumulation data were obtained from shallow firn cores, drilled during an overland traverse through a previously unknown part of Dronning Maud Land, East Antarctica. The traverse area is characterised by high mountains that obstruct the ice flow, resulting in a sudden transition from the polar plateau to the coastal region. The spatial variations of potential temperature, near-surface firn density and accumulation suggest that katabatic winds are active in this region. Proxy wind data derived from firn-density profiles confirm that annual mean wind speed is strongly related to the magnitude of the surface slope. The high elevation of the ice sheet south of the mountains makes for a dry, cold climate, in which mass loss owing to sublimation is small and erosion of snow by the wind has a potentially large impact on the surface mass balance. A simple katabatic-wind model is used to explain the variations of accumulation along the traverse line in terms of divergence/convergence of the local transport of drifting snow. The resulting wind- and snowdrift patterns are closely connected to the topography of the ice sheet: ridges are especially sensitive to erosion, while ice streams and other depressions act as collectors of drifting snow.
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; klimatologi; meteorologi